Pengaruh model pembelajaran inkuiri terbimbing dan media powerpoint berbasis hyperlink terhadap hasil belajar siswa pada materi larutan elektrolit dan nonelektrolit - Barus, Putri Carolin (ARKA INSTITUTE, 2022)
The guided inquiry learning model is a learning model that can make students more active in learning activities where students work together with their group friends to find answers to the problems given. This hyperlink-based PowerPoint media can attract students' attention where in this media we can show by clicking on the slide we want and in this media we can also show some learning videos that can attract students' attention in learning. This study aims to: (1) To find out whether the increase in student learning outcomes taught by guided inquiry learning models and hyperlink-based PowerPoint media is higher than the increase in student learning outcomes taught by conventional models and hyperlink-based PowerPoint media. (2) To determine student responses to the guided inquiry learning model and hyperlink-based PowerPoint media. This study involved an experimental class and a control class. From the posttest results, the average value of the experimental class students' learning outcomes was 86.07 and the control class was 76.78. From the results of N-gain, the percentage increase in learning outcomes for the experimental class is 81.06% and the control class is 68.18%. Based on the calculated value of N-gain, the increase in learning outcomes taught using the guided inquiry model and hyperlink-based PowerPoint media was higher than the increase in student learning outcomes taught using the conventional model and hyperlink-based PowerPoint media. Student responses to the guided inquiry learning model and hyperlink-based PowerPoint media on electrolyte and nonelectrolyte solutions have a percentage of 80.76% and are categorized as good.